Counter-Terrorism In Indonesia From The Perspective of The Human Security Approach - Brurry Hariyanto; Ramlani Lina Sinaulan; Amalia Syauket (KRTHA BHAYANGKARA, 2026)
Terrorism constitutes a multidimensional threat that not only disrupts state security but also endangers human rights, public safety, and societal well-being. Research on counter-terrorism in Indonesia has largely focused on state security approaches and law enforcement effectiveness, while comprehensive analyses from a human security perspective remain relatively limited. Addressing this gap, this study offers an analysis that integrates the human security paradigm as a framework for evaluating the effectiveness of Indonesia's counter-terrorism policies. The study aims to analyze the conceptualization and implementation of the human security approach in counter-terrorism efforts and to evaluate policy effectiveness based on parameters such as personal security protection, respect for human rights, community empowerment, and the sustainability of human security. Employing a normative legal research method, the study utilizes statutory and conceptual approaches, with data analyzed qualitatively through a literature review. The findings indicate that Indonesia's counter-terrorism policies have evolved through the strengthening of regulations, institutional frameworks, and prevention and deradicalization programs. However, when assessed against human security parameters, implementation remains predominantly oriented toward state security rather than comprehensive human protection. Therefore, policy strengthening is required to integrate state security and human security approaches, ensuring that counter-terrorism efforts are not only effective in maintaining national security but also capable of guaranteeing human rights protection, bolstering community resilience, and achieving sustainable security.